2023
DOI: 10.4251/wjgo.v15.i10.1829
|View full text |Cite
|
Sign up to set email alerts
|

Response to osimertinib in a colorectal cancer patient with an EGFR T790M mutation: A case report

Blake Buzard,
Lindsey Douglass,
Beth Gustafson
et al.

Abstract: Minimally invasive surgery is increasingly indicated in the management of malignant disease. Although oesophagectomy is a difficult operation, with a long learning curve, there is actually a shift towards the laparoscopic/thoracoscopic/ robotic approach, due to the advantages of visualization, surgeon comfort (robotic surgery) and the possibility of the whole team to see the operation as well as and the operating surgeon. Although currently there are still many controversial topics, about the surgical treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Moreover, Chang and colleagues showed that the depletion of miR-494 by a circular RNA contributes to cisplatin resistance [ 80 ]. Another possible aspect for future therapeutic considerations regarding miR-494 could be its use within combinatorial therapy strategies that can target more than one pathway of cancer cells; here, various kinase inhibitors, such as imatinib, sorafinib, trastuzumab, or osimertinib, already considered for dual therapy in CRC, would be interesting partners [ 81 , 82 , 83 , 84 ]. Towards this end, it has already been shown that miR-494 could play a critical role during imatinib treatment in resistant prostate cancer and CML leukemic stem cells [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Chang and colleagues showed that the depletion of miR-494 by a circular RNA contributes to cisplatin resistance [ 80 ]. Another possible aspect for future therapeutic considerations regarding miR-494 could be its use within combinatorial therapy strategies that can target more than one pathway of cancer cells; here, various kinase inhibitors, such as imatinib, sorafinib, trastuzumab, or osimertinib, already considered for dual therapy in CRC, would be interesting partners [ 81 , 82 , 83 , 84 ]. Towards this end, it has already been shown that miR-494 could play a critical role during imatinib treatment in resistant prostate cancer and CML leukemic stem cells [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting EGFR and its inhibition can prevent cancer growth by inducing apoptosis. Buzard et al [ 11 ] investigated the role of osimertinib, an EGFR targeted drug in a patient with metastatic sigmoid colon adenocarcinoma. The treatment for seven months resulted in an improvement in hepatic metastases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Buzard et al [ 11 ] investigated the role of osimertinib, an EGFR targeted drug in a patient with metastatic sigmoid colon adenocarcinoma. The treatment for seven months resulted in an improvement in hepatic metastases [ 11 ]. Bioinformatics plays a critical role in drug design, facilitating the discovery and development of new therapeutic agents in a more efficient and targeted manner.…”
Section: Introductionmentioning
confidence: 99%